Colorectal cancer molecular classification using BRAF, KRAS, microsatellite instability and CIMP status: Prognostic implications and response to chemotherapy. - Oscar Murcia; Míriam Juárez; María Rodríguez-Soler; Eva Hernández-Illán; Mar Giner-Calabuig; Miren Alustiza; Cecilia Egoavil; Adela Castillejo; Cristina Alenda; Víctor Barberá; Carolina Mangas-Sanjuan; Ana Yuste; et al. (PLoS ONE, 2018)
OBJECTIVE:The aim of this study was to validate a molecular classification of colorectal cancer (CRC) based on microsatellite instability (MSI), CpG island methylator phenotype (CIMP) status, BRAF, and KRAS and investigate each subtype's response to chemotherapy. DESIGN:This retrospective observational study included a population-based cohort of 878 CRC patients. We classified tumours into five different subtypes based on BRAF and KRAS mutation, CIMP status, and MSI. Patients with advanced stage II (T4N0M0) and stage III tumours received 5-fluoruracil (5-FU)-based chemotherapy or no adjuvant treatment based on clinical criteria. The main outcome was disease-free survival (DFS). RESULTS:Patients with the combination of microsatellite stable (MSS) tumours, BRAF mutation and CIMP positive exhibited the worst prognosis in univariate (log rank P<0.0001) and multivariate analyses (hazard ratio 1.75, 95% CI 1.05-2.93, P = 0.03) after adjusting for age, sex, chemotherapy, and TNM stage. Treatment with 5-FU-based regimens improved prognosis in patients with the combination of MSS tumours, KRAS mutation and CIMP negative (log rank P = 0.003) as well as in patients with MSS tumours plus BRAF and KRAS wild-type and CIMP negative (log-rank P<0.001). After adjusting for age, sex, and TNM stage in the multivariate analysis, only patients with the latter molecular combination had independently improved prognosis after adjuvant chemotherapy (hazard ratio 2.06, 95% CI 1.24-3.44, P = 0.005). CONCLUSION:We confirmed the prognostic value of stratifying CRC according to molecular subtypes using MSI, CIMP status, and somatic KRAS and BRAF mutation. Patients with traditional chromosomally unstable tumours obtained the best benefit from adjuvant 5-FU-based chemotherapy.